Pengaruh Sales Growth,Laba Bersih,Likuiditas Dan Leverage Terhadap Finansial Distress (Studi Perusahaan Sektor Manufaktur Yang Terdaftar Di BEI Tahun 2018 – 2021 ) - Phantohan Phantohan; Kartolo Hutabarat; Metania Cendana (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study intends to identify and analyze the impact of Sales Growth, Net Profit, Liquidity and Leverage on Financial Distress (a study of manufacturing sector companies on the IDX for the 2018-2021 period). The research approach uses a quantitative approach. The total population in the study was 193 manufacturing companies found on the IDX for the 2018-2021 period. The sample collection method was purposive sampling, companies that met the criteria for being sampled in this study totaled 14 companies. The results showed Sales growth, Net profit, Liquidity, and Leverage has a simultaneous and significant effect on Financial Distress (studies on manufacturing sector companies found on the IDX for the 2018-2021 period). The simultaneous test results state that Sales Growth partially has a significant effect on Financial Distress (studies on manufacturing sector companies listed on the IDX in 2018-2021). Simultaneous test results state that net profit partially has a significant effect on the occurrence of Financial Distress (studies in manufacturing sector companies listed on the IDX in 2018-2021). The simultaneous test results state that Liquidity partially has no significant effect on the occurrence of Financial Distress (studies of manufacturing sector companies listed on the IDX in 2018-2021). The simultaneous test results state that partial leverage has no significant effect on the occurrence of financial distress (a study of manufacturing sector companies listed on the IDX in 2018-2021. Keywords: Sales Growth, Net Profit, Liquidity, Leverage, Financial Distress